An Overview of New Methods in Plant Taxonomy - Vedi, Farida Shoaib (Journal of Natural Sciences – Kabul University, 2021)
Plant systematics is the scientific study of plant classification, which involves the identification, naming, and categorization of plants. This field focuses on comparing plant types and families and analyzing their relationships. The primary goal of classification is to establish a straightforward method for organizing plants. In the 19th century, classification efforts were based largely on physical characteristics, but modern scientists recognize the limitations of these purely observational and descriptive approaches. To create a comprehensive classification system, cytological, cytogenetic, anatomical, physiological, paleobotanical, and biochemical data should be incorporated. Today, additional fields such as cytotaxonomy, cytogenetics, and numerical taxonomy are employed in plant classification.